Household Demand for Food Prepared at Home and Food Away from Home in Indonesia - Damayanti, Ratih; Nuryakin, Chaikal; Muchtar, Pyan Amin (Economics and Finance in Indonesia, 2023)
This study aims to analyze the demand for food among Indonesian households, consisting of foods prepared at home (FPAH) and food away from home (FAFH). Utilizing longitudinal data from the National Socioeconomic Survey 2011-2013, combined with the Village Potential Statistics, the study estimates the demand with the Linear Approximated Almost Ideal Demand System (LA/AIDS). The results show that both FPAH and FAFH are normal goods, but FAFH is more elastic than FPAH. Additionally, in terms of income elasticity, we found that households show stronger responses in consumption on FAFH, compared to FPAH. We also present heterogeneity analysis on different types of household characteristics.